Phylotype Dynamics of Bacterial P Utilization Genes in Microbialites and Bacterioplankton of a Monomictic Endorheic Lake - Valdespino-Castillo, Patricia M; Alcántara-Hernández, Rocío J; Merino-Ibarra, Martín; Alcocer, Javier; Macek, Miroslav; Moreno-Guillén, Octavio A; Falcón, Luisa I (Microbial ecology, 2017)
Microbes can modulate ecosystem function since they harbor a vast genetic potential for biogeochemical cycling. The spatial and temporal dynamics of this genetic diversity should be acknowledged to establish a link between ecosystem function and community structure. In this study, we analyzed the genetic diversity of bacterial phosphorus utilization genes in two microbial assemblages, microbialites and bacterioplankton of Lake Alchichica, a semiclosed (i.e., endorheic) system with marked seasonality that varies in nutrient conditions, temperature, dissolved oxygen, and water column stability. We focused on dissolved organic phosphorus (DOP) utilization gene dynamics during contrasting mixing and stratification periods. Bacterial alkaline phosphatases (phoX and phoD) and alkaline beta-propeller phytases (bpp) were surveyed. DOP utilization genes showed different dynamics evidenced by a marked change within an intra-annual period and a differential circadian pattern of expression. Although Lake Alchichica is a semiclosed system, this dynamic turnover of phylotypes (from lake circulation to stratification) points to a different potential of DOP utilization by the microbial communities within periods. DOP utilization gene dynamics was different among genetic markers and among assemblages (microbialite vs. bacterioplankton). As estimated by the system's P mass balance, P inputs and outputs were similar in magnitude (difference was <10 %). A theoretical estimation of water column P monoesters was used to calculate the potential P fraction that can be remineralized on an annual basis. Overall, bacterial groups including Proteobacteria (Alpha and Gamma) and Bacteroidetes seem to be key participants in DOP utilization responses.
Keywords: Phosphorus Compounds; bakteriální RNA; sekvence nukleotidů; polymerázová řetězová reakce; životní prostředí; Oxygen; vodní organismy; genetická variace; Bacteroidetes; fylogeneze; fosfor; Ecosystem; Phosphorus; Lakes; Alkaline Phosphatase; Environment; voda; Phylogeny; Proteobacteria; Bacteria; alkalická fosfatasa; Microbial functional diversity; Phylotype seasonality; regulace genové exprese u bakterií; Sequence Analysis; jezera; Water; Phytase; genetické markery; DOP utilization; DNA, Bacterial; DNA bakterií; P turnover; kyslík; Aquatic Organisms; Genes, Bacterial; Mexico; roční období; sekvenční analýza; Seasons; Extracellular enzymes; sloučeniny fosforu; ekosystém; Polymerase Chain Reaction; Base Sequence; Genetic Variation; RNA, Bacterial; Genetic Markers; Mexiko; bakteriální geny; Gene Expression Regulation, Bacterial